An Association Between Paying Physician-teachers for their Teaching Efforts and an Improved Educational Experience for Learners - Ashar, Bimal (Springer-Verlag, 2007)
BACKGROUND: Medical schools often rely on faculty volunteerism to address clinical teaching needs for students. Increasing time pressures on physicians has made it difficult to secure commitments for clinical instruction. In the 2005–2006 academic year, the Johns Hopkins University School of Medicine (JHUSOM) launched the Colleges Program, recruiting 24 salary-supported physician-faculty to serve as advisors to students as well as teachers of the second year course, ‘clinical skills’. We hypothesized that compensating physician educators would have a measurable positive impact on the students’ experiences in this course. MATERIALS AND METHODS: Students’ assessments of paid colleges faculty (CF) preceptors from the 2005–2006 year were compared to those of volunteer preceptors from the two prior years (2003–2005 academic years) along six different teaching parameters linked to the course’s objectives. Multivariable regression analysis was used to identify the factors independently associated with higher preceptor scores. RESULTS: Fifty-eight preceptors taught clinical skills over the 3-year study period. The overall response rate for preceptor evaluations by medical learners was 77% (277/359). CF, more likely than volunteer preceptors to have a full-time academic appointment (100 vs 63%, p < .01), have an additional advanced degree (48 vs 15%, p < .01) and prior faculty development training (52 vs 17%, p < .01). Scores for all six evaluation domains were higher for CF compared to those from the two previous years combined (all p < .001). In the fully adjusted regression model, only CF status was independently associated with high preceptor evaluation scores (Odds Ratio 4.3, 95% CI 1.01–18.20). CONCLUSIONS: Salary support for teaching efforts in the time-intensive CS course coupled with the prestige of being appointed to the CF was associated with higher student evaluations.